Enforcement, Managerial Discretion, and the Informativeness of Accruals - Windisch, David (The European accounting review, 2021)
I examine the effect of strengthening the enforcement of financial reporting on managers' accrual decisions and the consequences for the informativeness of accruals. Using a sample of publicly listed German firms subject to a substantive enforcement change in 2005, I find that, consistent with the prior literature, the extent of managerial discretion in accruals declined after the introduction of the stricter enforcement regime. However, the findings on the predictive ability of accruals with respect to future cash flows and future earnings and the contemporaneous association between stock returns and accruals suggest that the informativeness of accruals also declined after the introduction of the stricter enforcement regime. This adverse effect is particularly strong when compared with a control group of publicly listed firms in Austria and Switzerland that operated in a similar institutional and economic environment but faced no substantive enforcement change. Overall, the findings suggest that stricter enforcement can have adverse consequences in the form of lower accrual informativeness.